1996
DOI: 10.1111/j.1532-5415.1996.tb01867.x
|View full text |Cite
|
Sign up to set email alerts
|

Life Values, Resuscitation Preferences, and the Applicability of Living Wills in an Older Population

Abstract: Subjects misinterpreted the applicability of living wills in nonterminal illness scenarios. A relationship between life values and resuscitation preferences was noted, which emphasizes the importance of eliciting and including life values when discussing advance directives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 16 publications
1
31
0
Order By: Relevance
“…These values include preferences for autonomous versus shared decision making (Blackhall et al, 1995), concern for individual versus family or community interests (Klessig, 1992), beliefs in sanctity of life or possibility of miracles (Klessig, 1992), and personal ideas about what makes life worth living versus intolerable (Ditto, Druley, Moore, Danks, & Smucker, 1996). Although there is evidence that values-related variables do correspond to decision outcomes (Fischer, Alpert, Stoeckle, & Emanuel, 1997;Schonwetter, Walker, Solomon, Indurkhya, & Robinson, 1996), there is mixed evidence regarding the stability of and relationship between values and treatment preferences through time (Ditto et al, 2003;Emanuel, Emanuel, Stoeckle, Hummel, & Barry, 1994;Lockhart, Ditto, Danks, Coppola, & Smucker, 2001). …”
Section: Va Author Manuscriptmentioning
confidence: 99%
See 3 more Smart Citations
“…These values include preferences for autonomous versus shared decision making (Blackhall et al, 1995), concern for individual versus family or community interests (Klessig, 1992), beliefs in sanctity of life or possibility of miracles (Klessig, 1992), and personal ideas about what makes life worth living versus intolerable (Ditto, Druley, Moore, Danks, & Smucker, 1996). Although there is evidence that values-related variables do correspond to decision outcomes (Fischer, Alpert, Stoeckle, & Emanuel, 1997;Schonwetter, Walker, Solomon, Indurkhya, & Robinson, 1996), there is mixed evidence regarding the stability of and relationship between values and treatment preferences through time (Ditto et al, 2003;Emanuel, Emanuel, Stoeckle, Hummel, & Barry, 1994;Lockhart, Ditto, Danks, Coppola, & Smucker, 2001). …”
Section: Va Author Manuscriptmentioning
confidence: 99%
“…Each item was rated on a 3-point scale, where 1 = influence not at all, 2 = influence a little, and 3 = influence a lot. Prior research found evidence of individual variability when asking people to rate the importance of various factors that might influence medical decisions or end-of-life care, as well as evidence of underlying constructs that such items tap (Doukas & Gorenflo, 1993;Karel, 2000;Karel & Gatz, 1996;Schonwetter et al, 1996;Steinhauser et al, 2000).…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, studies have suggested an overall need for enhanced public knowledge about end-of-life care (Marcoux et al 2007;Taylor et al 2003;Marco and Larkin 2003). Many patients welcome the opportunity to discuss their wishes (Stolman et al 1990;Hakim et al 1996;Gunasekera et al 1986;Schonwetter et al 1996;Uhlmann and Pearlman 1991).…”
mentioning
confidence: 94%